2016
DOI: 10.1103/physrevlett.117.177001
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Dirac Fermions on the Surface of a Noncentrosymmetric α -BiPd Superconductor

Abstract: Combining multiple emergent correlated properties such as superconductivity and magnetism within the topological matrix can have exceptional consequences in garnering new and exotic physics. Here, we study the topological surface states from a noncentrosymmetric α-BiPd superconductor by employing angle-resolved photoemission spectroscopy (ARPES) and first principle calculations. We observe that the Dirac surface states of this system have several interesting and unusual properties, compared to other topologica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
(63 reference statements)
3
20
0
Order By: Relevance
“…2(j)]. A similar observation was made earlier in the case of noncentrosymmetric BiPd [37]. There, it was suggested that the gap opening is due to the hybridization between the surface and the bulk states located in the same binding energy range.…”
Section: (D) Figs 2(e)-(h) Depict Edms Measured Using Various Photosupporting
confidence: 77%
See 1 more Smart Citation
“…2(j)]. A similar observation was made earlier in the case of noncentrosymmetric BiPd [37]. There, it was suggested that the gap opening is due to the hybridization between the surface and the bulk states located in the same binding energy range.…”
Section: (D) Figs 2(e)-(h) Depict Edms Measured Using Various Photosupporting
confidence: 77%
“…Interestingly, in addition to this, we have uncovered for the first time an another surface Dirac cone at the zone center with a node at ≈ 900 meV below E F . Much like in BiPd [37], the Dirac states at the zone center in PtBi 2 show a gap opening as a function of photon energy, possibly due to a surface-bulk hybridization. Based on these studies, we suggest that the linear MR observed in the hexagonal PtBi 2 could have originated from the linear dispersive surface states in the quantum limit, like in the case of topological insulators [2,3] where the large linear MR is observed only from the surface band structure.…”
mentioning
confidence: 92%
“…[20][21][22][23] While the data broadly agree, the interpretation of the band structure does not. Neupane et al 20 and Setti et al 22 place all surface states at the Γ point, consistent with their band structure calculations, whereas Benia et al 21 locate those below the Fermi level at the S point and those above the Fermi level at the Γ point, consistent with their own band structure calculations 19,21 . Here, we set out to address these differing interpretations, and clarify how they are related -tracing them back to the unit cell used for electronic structure calculations.…”
Section: Introductionmentioning
confidence: 84%
“…4) [13] and exhibits bulk type-II weak-coupling clean-limit superconductivity below T c = 3.7K [14][15][16][17][18][19][20]. Strong SOC has been clearly evidenced experimentally by means of angle-and spin-resolved photoemission spectroscopy (ARPES) [21][22][23][24] as well as scanning tunneling spectroscopy (STS) [24,25]. Furthermore, both experimental techniques revealed the presence of a surface Dirac state located at about 700 meV below the Fermi level and this has been supported by first-principle band-structure calculations [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%